PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 7 PARIAMAN - Widayanti, Ovi (Departemen Matematika, 2024)
One of the important competencies that students need to have is problem solving. However, the ability of students in class IX SMP Negeri 7 Pariaman is still not very good. Contextual Teaching and Learning (CTL) is an effective learning framework that should be applied to overcome this problem. Finding out whether the ninth grade students of SMP Negeri 7 Pariaman who used CTL model in their learning were more proficient than the direct learning was the main objective of this study. Using a static group design, this study utilized a pseudo-experimental type of research. Students of SMP Negeri 7 Pariaman TP 2024/2025 class IX took part. Classes IX.2 and IX.1 were selected as sample classes through a random selection process. The tool evaluated was the last word in quality control. The p-value for this study, was 0.016. The fact that the p-value is smaller than α means that the alternative hypothesis (H1) is acceptable. This data indicates that compared to the direct learning model, the CTL model performs better.Keywords– Contextual Teaching and Learning, mathematical problem solving skills, direct instruction